The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3102/0162373708317680
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Effectiveness in First Grade: The Importance of Background Qualifications, Attitudes, and Instructional Practices for Student Learning

Abstract: This study uses Early Childhood Longitudinal Study data to investigate the importance of three general aspects of teacher effects-teacher background qualifications, attitudes, and instructional practices-to reading and math achievement gains in first grade. The results indicate that compared with instructional practices, background qualifications have less robust associations with achievement gains. These findings suggest that the No Child Left Behind Act's "highly qualified teacher" provision, which screens t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
3
21

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(216 citation statements)
references
References 57 publications
9
176
3
21
Order By: Relevance
“…El estudio de Rosenthal y Jacobson (1968) fue pionero en demostrar tal efecto y en introducir el concepto de profecía auto-cumplida en contextos educativos, pues mostró que las expectativas de los profesores influyen directamente en el nivel de rendimiento de los alumnos. Si bien algunos aspectos metodológicos de este estudio han sido objeto de críticas, ha inspirado numerosas investigaciones que han reeditado y expandido sus hallazgos, revelando que las expectativas educativas de los docentes son un predictor del logro académico de sus estudiantes (Auwarter & Aruguete, 2008;Jussim & Eccles, 1992;Palardy, 1998;Palardy & Rumberger, 2008). Respecto a la manera en que esto opera, se ha encontrado que expectativas diferenciadas se traducen en prácticas de enseñanza diferenciadas, es decir, que los profesores tienden a actuar de acuerdo a sus creencias (Auwarter & Aruguete, 2008;Palardy, 1998;Palardy & Rumberger, 2008).…”
Section: El Rol Del Aula En La Socialización De Génerounclassified
“…El estudio de Rosenthal y Jacobson (1968) fue pionero en demostrar tal efecto y en introducir el concepto de profecía auto-cumplida en contextos educativos, pues mostró que las expectativas de los profesores influyen directamente en el nivel de rendimiento de los alumnos. Si bien algunos aspectos metodológicos de este estudio han sido objeto de críticas, ha inspirado numerosas investigaciones que han reeditado y expandido sus hallazgos, revelando que las expectativas educativas de los docentes son un predictor del logro académico de sus estudiantes (Auwarter & Aruguete, 2008;Jussim & Eccles, 1992;Palardy, 1998;Palardy & Rumberger, 2008). Respecto a la manera en que esto opera, se ha encontrado que expectativas diferenciadas se traducen en prácticas de enseñanza diferenciadas, es decir, que los profesores tienden a actuar de acuerdo a sus creencias (Auwarter & Aruguete, 2008;Palardy, 1998;Palardy & Rumberger, 2008).…”
Section: El Rol Del Aula En La Socialización De Génerounclassified
“…In fact, middle-class students tended to show summer gains in reading achievement. However, some recent research suggests that socioeconomic and ethnic achievement gaps do increase during the school year and not just over summer (Palardy, 2015;Palardy & Rumberger, 2008) and that year-school increases are due in part to differences in instructional practices and teacher effectiveness (Betts, Zau, & Rice, 2003;Murnane, Willett, Bub, & McCartney, 2006;Stipek, 2004). If, as these recent studies conclude, achievement gaps increase during the school year and teachers contribute to that increase, it is less clear whether VAA that include summer in will bias estimates against teachers and schools serving children from educationally disadvantaged backgrounds.…”
Section: Background Summer Learning and Achievement Gapsmentioning
confidence: 99%
“…In other words, although the teachers used the same methods to teach reading in Indonesian, they might have carried out the lessons differently. Several researchers have suggested that teachers' personality traits potentially affect students' achievements (Garrett, 2009;Palardy & Rumberger, 2008;Rimm-Kaufman & Sawyer, 2004) …”
Section: Discussionmentioning
confidence: 99%